2021
DOI: 10.4266/acc.2021.00213
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit professionals during the COVID-19 pandemic in Spain: social and work-related variables, COVID-19 symptoms, worries, and generalized anxiety levels

Abstract: Background: The severe acute respiratory syndrome coronavirus 2 outbreak has been identified as a pandemic and global health emergency. It presents as a severe acute respiratory disease. The rapid dissemination of the disease created challenges for healthcare systems and forced healthcare workers (HCWs) to deal with many clinical and nonclinical stresses. The aim of our research is to describe work conditions, symptoms experienced by HCWs, worries about contagion, and generalized anxiety symptoms and compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies, we showed that a safe predictive factors of anxiety, stress, and stress-coping tendencies (Cui et al, 2021;Garcia-Hedrera et al, 2021). The uncertainty about the pandemic increased EDRNs' job stress, emotional exhaustion, and depersonalization symptoms, and decreased their sense of personal accomplishment (Ahorsu et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies, we showed that a safe predictive factors of anxiety, stress, and stress-coping tendencies (Cui et al, 2021;Garcia-Hedrera et al, 2021). The uncertainty about the pandemic increased EDRNs' job stress, emotional exhaustion, and depersonalization symptoms, and decreased their sense of personal accomplishment (Ahorsu et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Sufficient PPE and clear guidelines are vital factors in maintaining a safe workplace for combating the pandemic (Chen et al, 2020; Jose et al, 2020; Liu, Luo, et al, 2020). The worry and fear of contracting the virus and passing it on to family members were the most influential and predictive factors of anxiety, stress, and stress‐coping tendencies (Cui et al, 2021; Garcia‐Hedrera et al, 2021). The uncertainty about the pandemic increased EDRNs' job stress, emotional exhaustion, and depersonalization symptoms, and decreased their sense of personal accomplishment (Ahorsu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These increases were related to healthcare workers undertaking activities that they do not usually do (Bellanti et al, 2021; Fernández‐Castillo et al, 2021; Gomez et al, 2020; Koh et al, 2005; Zhang, Xiang, & Alejok, 2021) or increasing work content (Jiang et al, 2022; Shoja et al, 2020), including changes to documentation (Fournier et al, 2022; Gomez et al, 2020), demand (Gomez et al, 2020; Tang et al, 2021; Villar et al, 2021; Wanninayake et al, 2022; Zamanzadeh et al, 2021; Zhan et al, 2020), skills required (Jiang et al, 2022; Liang et al, 2021; Tang et al, 2021; Wanninayake et al, 2022) and patient characteristics (Bruyneel, Gallani, et al, 2021; Felice et al, 2020), including isolation (Fernández‐Castillo et al, 2021). An increase in working overtime hours or more hours per day/week (Bellanti et al, 2021; Daneshvar et al, 2022; Duru, 2021; Evcili & Demirel, 2022; Fournier et al, 2022; Gao et al, 2020; Koh et al, 2005; Malinowska‐Lipień et al, 2021; Matsuo et al, 2021; Niu et al, 2022; Ozkan & Unlu, 2021; Ren et al, 2022; Said & El‐Shafei, 2021; Sethi et al, 2020; Zhan et al, 2020; Zhang, Xiang, & Alejok, 2021), an increase in healthcare provider‐patient ratios (Bergman et al, 2021; Bruyneel, Smith, et al, 2021; Cheong et al, 2022; Evcili & Demirel, 2022; García‐Hedrera et al, 2021; González‐Gil et al, 2021; Hoogendoorn et al, 2021; Ren et al, 2022; Scott et al, 2022), staffing shortages (Brophy et al, 2021; Evcili & Demirel, 2022; Fournier et al, 2022; González‐Gil et al,…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Bruyneel, Gallani, et al (2021) and Hoogendoorn et al (2021) identified that nursing activity scores were higher among the COVID‐19 patients as they required more time, which increased nursing workloads. However, some of the participants in these studies also reported a reduction in their workloads (Akova et al, 2022; Arslan et al, 2021; Butera et al, 2021; Felice et al, 2020; García‐Hedrera et al, 2021; Li et al, 2021; Matsuo et al, 2021; Nahidi et al, 2022; Scott et al, 2022). For example, Butera et al (2021) identified that 2.3% of nurses in the ICU and 37% in the emergency department reported a decrease in workload.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has pointed out the psychoemotional consequences experienced by nurses in Critical Care Units (CCU) as a consequence of the COVID-19 [1][2][3] pandemic. These consequences have been associated with several risk factors such as fear of contagion, caring for infectious patients, working in specialized units such as the CCU [4,5], or the fact of being a mother and a nurse in the CCU [6]. A recent meta-analysis in nurses reported prevalent rates of stress, anxiety and depression of 43%, 37% and 35%, respectively [7].…”
Section: Introductionmentioning
confidence: 99%